Pengembangan Aplikasi Sistem Penjualan Kaos Berbasis Android Untuk Usaha Konveksi - Mustova, Royyan; Pramudwiatmoko, Arif (Institut Informatika Dan Bisnis Darmajaya, 2024)
The advancement of information technology in the era of globalization has opened up new business opportunities through electronic transactions. This is regulated in Law Number 7 of 2014 concerning Trade, which drives the rapid development of e-commerce. The internet and information technology, especially Android devices, have changed people's shopping patterns as well as the way manufacturers promote their products. An example is Rfour Clothing, a fashion business from Wonogiri that focuses on selling truck-themed t-shirts. To overcome the obstacles in offline sales methods and untidy transaction recording, researchers developed an Android-based application for Rfour Clothing with the Rapid Application Development (RAD) method that presents online ordering features, payment gateways, and web based admin dashboards used to manage goods and manage transaction results, so that they can support future business growth; further research is recommended to improve the quality of the interface, add notification features, and strengthen application security to provide a user experience